2016
DOI: 10.1080/13548506.2016.1153682
|View full text |Cite
|
Sign up to set email alerts
|

A randomized-control trial for the teachers’ diploma programme on psychosocial care, support and protection in Zambian government primary schools

Abstract: Orphaned and vulnerable children (OVC) experience poverty, stigma, and abuse resulting in poor physical, emotional, and psychological outcomes. The Teachers' Diploma Programme on Psychosocial Care, Support, and Protection is a child-centered 15-month long-distance learning program focused on providing teachers with the knowledge and skills to enhance their school environments, foster psychosocial support, and facilitate school-community relationships. A randomized controlled trial was implemented in 2013-2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Of the 100 evaluations included in our meta-analysis of school-based anti-bullying programs, the majority (80 for perpetration, 84 for victimization) were conducted in one of 12 different countries (i.e., Australia, Canada, Cyprus, Finland, Germany, Greece, Italy, Netherlands, Norway, Spain, UK, USA). We also identified singular evaluations conducted in Austria (Yanagida et al 2016);Brazil (da Silva et al 2016); China (Ju et al 2009); Czechoslovakia (modern day Czech Republic and Slovakia; Rican, Ondrova, and Svatos 1996); Hong Kong (Wong et al 2011); Ireland (O'Moore and Minton 2004); Malaysia (Yaakub et al 2010); Romania (Trip et al 2015); Sweden (Kimber et al 2008); South Africa (Meyer and Lesch 2000); Switzerland (Alsaker and Valkanover 2001); and Zambia (Kaljee et al 2017).…”
Section: Evaluations Globallymentioning
confidence: 99%
“…Of the 100 evaluations included in our meta-analysis of school-based anti-bullying programs, the majority (80 for perpetration, 84 for victimization) were conducted in one of 12 different countries (i.e., Australia, Canada, Cyprus, Finland, Germany, Greece, Italy, Netherlands, Norway, Spain, UK, USA). We also identified singular evaluations conducted in Austria (Yanagida et al 2016);Brazil (da Silva et al 2016); China (Ju et al 2009); Czechoslovakia (modern day Czech Republic and Slovakia; Rican, Ondrova, and Svatos 1996); Hong Kong (Wong et al 2011); Ireland (O'Moore and Minton 2004); Malaysia (Yaakub et al 2010); Romania (Trip et al 2015); Sweden (Kimber et al 2008); South Africa (Meyer and Lesch 2000); Switzerland (Alsaker and Valkanover 2001); and Zambia (Kaljee et al 2017).…”
Section: Evaluations Globallymentioning
confidence: 99%
“…Furthermore, these data show program changes that teachers are making in their classrooms and schools. These qualitative data in combination with the randomized controlled trial data (Kaljee et al, 2016) support the need for school-based psychosocial support systems as a part of broader community-based interventions to facilitate teachers' abilities to support students and their families and increase child resiliency.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes from the trial indicate that intervention teachers reported positive change in relation to emotional self-care, use of teaching resources, classroom and school safety, school physical environment, social support, and gender equity for boys and girls. Intervention student data indicate positive changes for future orientation, school respect and support, school safety, school physical environment, response to sexual abuse, and bullying behaviors (Kaljee et al, 2016).…”
Section: Quantitative Evaluation Of the Teachers' Diploma Programmentioning
confidence: 99%
“…A number of authors [2,13,24,32] studied psychological protection mechanisms of adolescents with different behavioral styles in conflict. The authors determined that leading mechanisms of psychological protection are replacement and intellectualization.…”
Section: Introductionmentioning
confidence: 99%